2011
DOI: 10.1039/c0dt01040e
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and structures of the first terminal phosphanylphosphido complex of hafnium [Cp2Hf(Cl){η1-(Me3Si)P–P(NEt2)2}] and the first zirconocene-phosphanylphosphinidene dimer [Cp2Zr{μ2-P–P(NEt2)2}2ZrCp2]

Abstract: Reactions of (Et(2)N)(2)P-P(SiMe(3))Li with [Cp(2)MCl(2)] (M = Zr, Hf) in toluene or pentane yield the related terminal phosphanylphosphido complexes [Cp(2)M(Cl){η(1)-(Me(3)Si)P-P(NEt(2))(2)}]. The solid state structure of [Cp(2)Hf(Cl){η(1)-(Me(3)Si)P-P(NEt(2))(2)}] was established by single crystal X-ray diffraction. The reaction of (Et(2)N)(2)P-P(SiMe(3))Li with [Cp(2)ZrCl(2)] in THF or DME solutions leads to the formation of deep red crystals of the first neutral diamagnetic zirconocene-phosphanylphosphinid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…We pay special attention to the t Bu 2 P–P moiety, because this group is a ligand in the majority of known phosphanylphosphinidene transition‐metal complexes , . Our calculations performed for this phosphinidene indicate a singlet ground state.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We pay special attention to the t Bu 2 P–P moiety, because this group is a ligand in the majority of known phosphanylphosphinidene transition‐metal complexes , . Our calculations performed for this phosphinidene indicate a singlet ground state.…”
Section: Resultsmentioning
confidence: 99%
“…These compounds react with electrophilic R 2 PCl to yield neutral niobium and cationic tungsten complexes with side‐on bonded t Bu 2 P–P and Ph 2 P–P ligands (Scheme B). We have demonstrated that lithiated diphosphanes are effective precursors of phosphanylphosphinidene ligands in reactions with chlorido complexes of zirconium(IV),, , platinum(II), tungsten(VI),, molybdenum(VI), and titanium(IV) (Scheme C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, for the t Bu-substituted diphosphane only one of the chloride ligands was replaced, generating the phosphinidene complex 15, in which the P-P t Bu 2 ligand is coordinated in a side-on mode and the P atom displays a non-planar geometry (Scheme 8) [24]. In contrast, the bis(phosphinidene) complex 16 was obtained instead when using the NEt 2 -substituted reagent; moreover, other products were obtained in these reactions when changing the solvent [25].…”
Section: Related Processesmentioning
confidence: 98%
“…The influence of the metal in these reactions was also notable, since analogous reactions with [HfCl 2 Cp 2 ] failed to yield any phosphinidene complex [25], while reaction of [WCl 2 Cp 2 ] with Li[(SiMe 3 )P-P i Pr 2 ] yielded the cyclopentadienylidene-phosphinidene complex [W 2 Cp 2 (μ-κ 1 :κ 1 ,η 5 -A similar silyl redistribution process following the salt metathesis step has been invoked by Chen and co-workers to explain the formation of the neodymium bis(phosphinidene) complex (17) in the reaction of [NdI 3 (THF) 3.5 ] with K[P(SiMe 3 )(DIPP)] (DIPP = 2,6-i Pr 2 C 6 H 3 ; Scheme 9) [27]. This paramagnetic compound could be characterised in the solid state and exhibits two phosphinidene ligands with an almost perfectly trigonal planar geometry around the P atoms.…”
Section: Related Processesmentioning
confidence: 99%